ON INEXTENSIBLE FLOWS OF ?1 BISHOP SPHERICAL IMAGES WITH TYPE-2 BISHOP FRAME - Korpinar, Talat; Asil, Vedat; Korpinar, Zeliha (Editura Bibliotheca-Bibliotheca Publ House, 2020)
In this paper, we study Pi(1) Bishop spherical images according to type-2 Bishop frame. Using the type-2 Bishop frame of the given curve, we present partial differential equations. We give some characterizations for curvatures of a curve in space.
Keywords: Type-2 Bishop frame; Curvatures; Flows